(untitled) (Research, Society and Development, 2022)
Feline sporotrichosis is a subcutaneous, infectious, and contagious mycosis, with zoonotic characteristics. Until now there are no reports on the isolation of Sporothrix sp. in cats in the state of Pará. The present work aimed to isolate Sporothrix spp. from a cat with possible zoonotic involvement in the city of Belém, Pará. Through the active search for suspected cases of sporotrichosis, carried out by members of the Center for the Control of Zoonoses of Belém (CCZ, Belém) the suspicion of the disease in a feline was reported, with probable transmission to its owner. Clinical evaluation was performed, and biological material was collected from the animal for identifying the agent. Microscopic evaluation of the collected sample and microbial culture confirmed the presence of Sporothrix sp. in the sample. This study is the first to report the microbiological isolation of Sporothrix sp. in a cat in the metropolitan region of Belém, Pará, with possible zoonotic transmission. This indicates a probable underreporting of cases, an unknowing regarding the reality of health conditions and the need for more accurate and comprehensive evaluation of sporotrichosis in this region.